Comparison of quality and organization of physical activities organized by University Sports Association at selected universities of the Upper Silesia - Michalina Dyla; Michał Rżany; Aleksandra Rzadkowska; Krzysztof Suszyński; Dariusz Górka (Nicolaus Copernicus University in Toruń, 2015)
Introduction. Gym exercises have become more and more popular in the recent years. Thus, it is not surprising that this form of physical activity offered by University Sports Association has become a popular choice among the university students. However, to benefit from the workout, the exercises must be performed correctly. Application of excessive loads, number of repetitions, or poor technique can cause injury, which may lead to serious physical damage. Aim. The aims were to check the quality and organization of physical activities ogranized by University Sports Association in chosen universities of the Upper Silesia. The questions asked were: 1. Is there a correlation  between different universities and the health control among new students at the gym? 2. Does the type of university correlate with the quality of the workout? 3. Is there a correlation between the type of university and the duration of the strength training? Materials and Methods. 120 students were examined, among which there were 44 women aged 17 to 24 (x=20,8;SD= 1,8) and 76 man aged 17 to 28 (x=21,8; SD= 1,9). They were university students from the following Upper Silesian universities: ŚUM, AWF, UŚ and UE, who regularly practise gym exercises organized by Academic Sports Association. An original questionnaire was created for the purpose of this study. The questions concerned participation in the gym activities, choice of exercises in context of their health predispositions, presentation of the proper technique of exercises, information about synchronization exercises with breath and quality control of performed exercises without prior request of the students. Statistical analysis was performed by a program Statistica. Results. Analysis of variance (ANOVA) demonstrated a statistically significant relation between the type of university and the health control among new students at the gym (p=0,005). ŚUM is the university where the students are the most often controlled. There is no correlation between the type of university and the quality of the training (p=0,35). The duration of strength training is not correlated with the type of university. Students of AWF Katowice spend the most time at the gym, whereas students from ŚUM Katowice spend the least. Conclusion 1. Frequency of the health control among students starting classes at the gym depends on the type of university. 2.  The type of university does not affect the quality of the training. 3.  The duration of training does not depend on the type of university.